Dynamic pharmacy leadership during the COVID-19 crisis: Optimizing patient care through formulary and drug shortage management. (23rd July 2020) - Pulk, Rebecca Ann; Leber, Molly; Tran, Lydia; Ammar, Mahmoud; Amin, Nilesh; Miller, LeeAnn; Yazdi, Marina
Abstract: Purpose: The coronavirus disease 2019 (COVID-19) pandemic has created unprecedented challenges for health systems around the world. We describe our approach to adapting the pharmacy leadership structure to address critical medication shortages through innovative data analysis, procurement strategies, and rapid implementation of medication policy. Summary: Yale New Haven Health deployed a system incident management command structure to effectively respond to the COVID-19 crisis. System pharmacy services adopted a similar framework to enable efficient communication and quick decision-making in key domains, including drug procurement and policy. By refining a model to project health-system medication needs, we were able to anticipate challenges and devise alternative treatment algorithms. By leveraging big data and creating a system knowledge base, we were able to consolidate reporting and coordinate efforts to ensure system success. Various procurement strategies were employed to ensure adequate supply, including frequent communication with our wholesaler, sourcing direct from suppliers, outsourcing of sterile products compounding to registered 503B outsourcing facilities, and acquisition of active pharmaceutical ingredients for compounding of essential medications. Strategic positioning of pharmacists within the health system's incident command response teams and rapid adaption of drug use policy governance fueled accelerated response and nimble implementation. Communication was streamlined and executed via multiple outlets to reach a broad audience across the health system. Conclusion: With medication shortages posing a threat to patient care, dynamic pharmacy leadership proved essential to providing patient care at the height of the COVID-19 pandemic. System alignment and the rapid adaption of the existing framework for drug shortage management and medication use policy were crucial to success in crisis response.